MAKNA ZIARAH MAKAM HABIB ANIS AL-HABSYI BAGI MASYARAKAT NU SURAKARTA - Aly Mashar (IAIN Surakarta, 2017)
Habib Anis al-Habsyi is one of the most respected scholars not only in the environment where he lives,Â Pasar Kliwon, Surakarta, but also by Muslims outside the city of Surakarta and even Foreign Affairs. Therefore, even though he has died in 2006, still busy coming to him, exactly is to his grave located in a booth at the Riyadh mosque complex, Pasar Kliwon, Surakarta. On this basis, the research would like to examine what the motivation of the pilgrims to the Habib Anis Tomb. This research model is qualitative and using descriptive-interpretative approach. The theoretical framework that used is the theory of motivation, charisma, and barakah. The result of this research is that the pilgrim's motivation is the same as the pilgrims in other sacred tombs i.e looking for Blessings. But what distinguishes is the perception of Habib Anis's authority is not based on the karomahs that he has, but more on his personality and noble character. In short, the motivation of pilgrims to the tomb of Habib Anis is a unique series between charisma, kewalian, and barakah.